Cornelli, G. (2013). In Search of Pythagoreanism. Pythagoreanism as an Historiographical Category, “Studia Praesocratica” 4, de Gruyter, Berlin - Stavru, Alessandro (Revista Archai, 2014)
CORNELLI, G. (2013). In Search of Pythagoreanism. Pythagoreanism as an Historiographical Category, “Studia Praesocratica” 4, de Gruyter, Berlin